Crime, violence and modernity towards a contemporary sociological criminology - Hughes, Gordon, 1952- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
This book makes an original contribution to reconnecting criminological inquiry to the core concerns of the classical sociological imagination and to the intellectual resources of comparative and historical sociology. Throughout the book Hughes challenges the long-standing division of labour in criminology and sociology more generally between theory', method' and research'. Accordingly, the author's concerns here are as much about the craft and working methods of being a sociological criminologist as it is about theory and concepts. In the first half of the book, the key conceptual and methodological premises of the classical sociological tradition are outlined and the latter's potential for revitalizing contemporary criminological research-theorizing are assessed. These chapters also address the debate regarding the relationship between crime and violence, and that of modernity and the Western civilizing process'. In the second half of the book, three areas of current criminological inquiry are explored through the lens of the long-term, process-oriented and radically relational perspective of contemporary Weberian and Eliasian scholarship. Among the areas of comparative investigation explored here are street crime, gangs and urban violence, genocide and murderous ethnic cleansing, warfare, colonialism and human rights. Written in a clear and direct style this book will appeal to students and scholars of criminology, sociology and all those interested in what a sociological lens brings to the practices of contemporary criminology.
Sociology and criminology: a rapprochement -- Classical sociology and the criminological imagination: some core principles and concepts -- Violence, civilization and modernity: connecting historical sociology and contemporary criminology -- Theory, method and evidence in criminological research: classical traces and contemporary developments -- Critique and normative deliberation in criminology: value involvement and detachment revisited -- Street crime, violence and young men in late modernity -- The dark side of modernity? Genocide, ethnic cleansing and state crime -- Organizing brutality, human rights and the modern global order: beyond the civilizing process?
Keywords: POLITICAL SCIENCE / Political Freedom & Security / Human Rights; SOCIAL SCIENCE / Criminology; Criminology; Crime -- Sociological aspects